Red Gram Agro Advisory System - Arjunagi, SY; Patil, NB (International Journal of Computer Sciences and Engineering, 2025)
Agriculture is very helpful to meet the basic needs of human and their civilization by providing food, clothing, shelters, medicine and recreation. Hence, agriculture is the most important enterprise in the world. Agriculture provides a free fare and fresh environment, abundant food for driving out famine; favours friendship by eliminating fights. Red gram production is major plant or seed in world. Average world production of red gram is at 3.0 million tons in the last six years (2000-05). The area under cultivation is stagnant at 4.5 million hectares in the same period. Red gram is drought resistant and can be grown in areas with less than 650 mm annual rainfall. Production of red gram is estimated at 46,000 km² in all over world. Around 82% of this is grown in India. Hence it is necessary to develop android application for red gram crop. It is helpful for farmer to have all information related to red gram crop. This app will contain crop information and disease related to crop.